Bicuspid aortic valve repair with hemi-remodeling technique and external ring annuloplasty - Carlotta, Brega; Zakkar, Mustafa; Zacek, Pavel; Palladino, Michele; Lansac, Emmanuel (Journal of cardiac surgery, 2020)
BACKGROUND: Current guidelines recommend root replacement when diameter of the sinuses of Valsalva are superior to 45 mm particularly for bicuspid valve. However, in case of tubular aorta aneurysms with moderate root dilatation (40-45 mm diameter), the approach is still debated regarding the increased risk of coronary reimplantation. We present a modified hemi-remodeling aortic repair technique that includes the replacement of the noncoronary sinus, ascending aorta, and valve repair with external ring annuloplasty in patients with bicuspid aortic valve (BAV) and moderately dilated aortic root. METHODS: Between 2003 and 2017, 18 patients presenting with left-right BAV and an aortic root diameter at 42.3+/-3.3 mm underwent hemi-root and ascending aorta replacement and aortic valve repair with external annuloplasty. RESULTS: Postoperatively, 16 (88.9%) had no aortic insufficiency (AI) and 2 (11.1%) had grade I AI, no patients had grade III or grade IV AI. Overall survival and freedom from grade II AI at 4 years and freedom from aortic valve-related reoperation were 100%. CONCLUSION: The standardized modified hemi-remodeling technique we present is a safe and reproducible procedure, with satisfactory durability at follow-up. This technique represents an interesting alternative to full valve sparing root replacement, as it avoids the operative risk of coronary reimplantation, allows shorter cross-clamping time and a better exposition on the valve for a symmetrical repair, placing the commissure at 180°, compared with valve sparing root replacement.
Keywords: Cardiac Valve Annuloplasty; Aortic Valve; Heart Valve Diseases; nemoci srdečních chlopní; aortální chlopeň; anuloplastika srdeční chlopně